Nilai-Nilai Pendidikan Karakter dalam Novel Di Antara Dua Sujud Karya Muhammad Irata - Yuliza Efendi; Andria Catri Tamsin (Universitas Negeri Padang, 2023)
ABSTRACT The purpose of this research is to describe the values of character education in the novel Di Antara Dua Sujud by Muhammad Irata. This type of research is qualitative using descriptive method. This study uses a mimetic approach. The data in this study are data about the values of character education contained in the novel Di Antara Dua Sujud by Muhammad Irata. The data is in the form of phrases, words and sentences contained in the novel Between Two Sujud. The data source in this study is Between Two Sujud by Muhammad Irata, which was published in 2017 by Mutiara Media with 412 pages thick. The research instrument was the researcher himself with the additional help of a recording sheet format. Data collection techniques include reading repeatedly, recording data, and classifying data related to character education values in the novel Di Antara Dua Sujud by Muhammad Irata. The data analysis technique is a qualitative description technique. Based on the results of data analysis and discussion, eight types of character education values were found in the novel Di Antara Dua Sujud by Muhammad Irata. First, the value of honest character education. Second, the value of character education is curiosity. Third, the value of hard work character education. Fourth, the value of friendly character education. Fifth, the value of peace-loving character education. Sixth, the value of character education is fond of reading. Seventh, the value of social care character education. Eighth, the value of responsibility character education. Keywords: Nilai, Pendidikan Karakter, Novel Di Antara Dua Sujud